TEKNIK PEMBALIKAN KONSELING GESTALT PADA SISWA INTROVERT - Fatimah Setiani; Agus Heriyanto; Waita Waita (STKIP MUHAMMADIYAH SAMPIT, 2020)
Personality problems are very closely related to one’s self, as is the nature of introverted. If the introverted is owned by someone, it will cause him to become someone who is vindictive, unable to establish relationship with other people and will have difficulty communicating well.This study aims to overcome children who have introverted nature by applying Gestalt counseling models with reversal techniques. Intake of data is using qualitative descriptive methods with case study approach.The results of this study indicate that the application of the Gestalt counseling model with reversal techniques successfully composed student who have introverted traits. There is a decrease in introverted characteristics from high category to low category after carrying out individual counseling.